2020
DOI: 10.1007/s00586-020-06613-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence facilitates decision-making in the treatment of lumbar disc herniations

Abstract: Purpose Apart from patients with severe neurological deficits, it is not clear whether surgical or conservative treatment of lumbar disc herniations is superior for the individual patient. We investigated whether deep learning techniques can predict the outcome of patients with lumbar disc herniation after 6 months of treatment. Methods The data of 60 patients were used to train and test a deep learning algorithm with the aim to achieve an acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The reason for the insufficient prediction rate is not the number but the quality of the data [18]. We showed previously that a good prediction is possible even with small groups if the data quality is appropriate [19]. The present study is a preliminary study using prospectively collected registry data generated in daily clinical routine.…”
Section: Prediction Of Efficiancy Of Conservative Treatment Of Back Painmentioning
confidence: 90%
“…The reason for the insufficient prediction rate is not the number but the quality of the data [18]. We showed previously that a good prediction is possible even with small groups if the data quality is appropriate [19]. The present study is a preliminary study using prospectively collected registry data generated in daily clinical routine.…”
Section: Prediction Of Efficiancy Of Conservative Treatment Of Back Painmentioning
confidence: 90%
“…However, regression models showed the worst efficiency treatment rate for each of clinical outcomes. The implementation of deep learning technology in the study by Wirries et al [ 21 ] contributed to exact prediction of a patient’s functional status by ODI 6 months both after lumbar microdiscectomy and in case of conservative treatment. Using prospective register data (n=635), Siccoli et al [ 22 ] demonstrated a model based on several ML algorithms to enable to provide preoperative planning of the following results: clinical ODI improvement, pain decrease in legs and in spine 12 months after surgery — within the accuracy of 62, 74, and 66%, respectively; reduction of the total number of reoperations — within the accuracy of 69%, and surgery time — within the accuracy of 78%; the reduced length of hospital stay — within the accuracy of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in surgical robotic systems, artificial reality, and artificial intelligence (AI) are eyeopening. [32][33][34][35] To date, doctors have been responsible for surgical decisions and surgery, but the outcomes are heterogeneous, probably due to diverse decision-making processes and surgical expertise. 6,13,22,[24][25][26] The expectation for AI and robotic systems is precision medicine, and with the development of new technology, decisionmaking and surgical procedures could be replaced by AI and robots in the near future.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…6,13,22,[24][25][26] The expectation for AI and robotic systems is precision medicine, and with the development of new technology, decisionmaking and surgical procedures could be replaced by AI and robots in the near future. [33][34][35] We cannot stop evolution, but we can work toward systematic, reproducible, reliable, and precise surgical decisions and skills with AI and robotics.…”
Section: Future Perspectivesmentioning
confidence: 99%